(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Bankura is mainly an agriculture-based district in the west of the state West Bengal. It is called a backward district but it is really proud of having its fighting farmers who love their lands as ‘Maa Lakshmi’ and cultivate many essential things with hard-labour.